FTIR Investigation of Structural Change Due to Radiation Damage in Biomolecule - Dutta, Arup; Sarkar, A. (Asian Journal of Chemistry, 2011)
The objective of this paper is the development of an over dynamical characterization of biomolecules under the purview of this work. The developed sucrose specimen was supposed to exhibit change in molecular structure over that in pure sucrose due to rapture of some bonds. FTIR analysis on pure sucrose was carried out to examine its molecular structure and dynamical information. Infrared absorption spectrum of sucrose was analyzed from measured data of FTIR spectra. The change in characteristics bond stretching due to radiation damage is detected clearly. Some characteristics frequencies are absent due to radiation damage by irradiation of laser beam having energy greater than the bond strength of sucrose. The FTIR analysis successfully confirms the effect of radiation damage of sucrose molecule due to irradiation laser on it. The laser irradiation on pure Sucrose molecule caused damage, in its molecular structure and its finger print is detectable from FTIR study.